2008
DOI: 10.1111/j.1574-6941.2008.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Ixodes ricinus tick-associated bacterial communities from different forests

Abstract: Nymphal Ixodes ricinus ticks (n=180) were collected from three different areas in the Netherlands to investigate the effect of forest composition on tick-associated microbial communities. Sampled habitats differed in thickness of leaf litter and humus layers and vegetation associations and were located near Amsterdam (Beech-Oak), Ede (Birch-Oak) and Veldhoven (Birch-Oak). Analysis of nine 16S rRNA gene clone libraries made from individual ticks showed nearest matches with presumed pathogens Candidatus Neoehrli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 60 publications
2
77
0
Order By: Relevance
“…In the Netherlands and Russia, "Ca. Neoehrlichia mikurensis"-infected I. ricinus ticks appeared to be somewhat more common (1,17,21). A related, if not identical pathogen, designated "Ca.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands and Russia, "Ca. Neoehrlichia mikurensis"-infected I. ricinus ticks appeared to be somewhat more common (1,17,21). A related, if not identical pathogen, designated "Ca.…”
Section: Discussionmentioning
confidence: 99%
“…related to the typhus group in I. ricinus ticks that were collected in the Netherlands (311,331). Another such example is R. helvetica in D. reticulatus ticks in Croatia (287).…”
Section: Nonvalidated Incompletely Described or Uncultivated Speciesmentioning
confidence: 99%
“…Diverse microbial communities were found in these vectors, and most microbial species were represented sparsely or occurred in only a few individual vectors. Some studies also indicated that the composition of these microbial communities often varies across time and space (Kirstein et al, 1997;Wielinga et al, 2006;van Overbeek et al, 2008;Jones et al, 2010) and that these variations are linked largely to the characteristics of the arthropod (for example, its species, life stage, diet and blood engorgement level; Pidiyar et al, 2004;Moreno et al, 2006;Heise et al, 2010;Jones et al, 2010;Hawlena et al, 2013). Nevertheless, because vector-borne microbes spend a part of their lives in the blood of the vertebrate host, it is important to consider also the internal environment of this host.…”
Section: Introductionmentioning
confidence: 99%